Assessment of Concrete Susceptibility to Fire Spalling: A Report on the State-of-the-art in Testing Procedures. (2015) - Krzemień, Katarzyna; Hager, Izabela
Abstract: The assessment of concrete behavior at high temperature is done by a variety of tests carried out on specimens of different sizes. Small-scale tests examine concrete's behavior when exposed to elevated temperature, while full-scale fire tests are carried out on full-sized concrete elements in which the boundary conditions, external load and conditioning correspond to design assumptions. Complementary to these is the medium-scale test carried out on a portion of a slab's surface area which has been exposed to fire, ca. 1m 2 . Such medium-scale tests are often used as a cost-effective solution to verify the behavior of a specific concrete mix in fire conditions. This paper reviews the existing furnaces, testing procedures and laboratory setups used to assess a material's tendency to spall. Its objective is to emphasize the need to unify spalling risk assessment procedures by establishing recommended guidelines for testing.